The Catalogue of Gamma-Ray Burst Observations by HEPD-01 in the 0.3–50 MeV Energy Range - S. Bartocci; R. Battiston; S. Beolè; W. J. Burger; D. Campana; P. Cipollone; A. Contin; M. Cristoforetti; C. De Donato; C. De Santis; A. Di Luca; F. M. Follega; et al. (The Astrophysical Journal)
The High-Energy Particle Detector (HEPD-01) on board the China Seismo-Electromagnetic Satellite, located on a Sun-synchronous orbit at 500 km of altitude with an inclination of 97°, features a dedicated logic counting low-energy event rates, which proved sensitive to intense Gamma-Ray Burst (GRB). The present work reports a comprehensive analysis of signals induced by GRBs in the event-rate data collected between 2018 August and 2022 June. After accurately modeling the background rate as observed in different passages of the satellite over the same geographical area, we detected significant deviations to be compared with observations of GRB candidates from other observatories. The analysis revealed 12 statistically significant excesses, that have been associated with GRB 181222B, GRB 190114C, GRB 190129B, GRB 190305A, GRB 190928A, GRB 200412B, GRB 200422A, GRB 200826B, GRB 201009A, GRB 210702A, GRB 211211A, and GRB 220624A. We report light curves for 0.3–50 MeV photons, comparing them with findings from other space telescopes. The catalog of observations is published, complete of GRB observation time, duration, integrated counts, and fluence.